The Sources of Belief in Personal Capability: Antecedents of Self‐Efficacy in Private Adaptation to Flood Risk. Issue 10 (15th June 2020) - Seebauer, Sebastian; Babcicky, Philipp
Abstract: Self‐efficacy is one of the strongest and most consistent drivers of private flood mitigation behavior; however, the factors influencing self‐efficacy in the context of flooding remain unclear. The present study examines three potential antecedents of self‐efficacy: personal and vicarious experiences of floods or building‐related events, social norms for private flood preparedness, and personal competencies such as technical abilities and social skills. While controlling for other drivers in a protection motivation theory (PMT) framework, these antecedents are tested as precursors of self‐efficacy and intentions to improve flood resilience. Structural equation modeling is applied to conduct mediation analyses with survey data of 381 flood‐prone households in Austria. Contrary to theoretical expectations, personal and vicarious experiences do not predict self‐efficacy, presumably because rare flood events and changing hazard characteristics do not facilitate generalizable performance accomplishments. Social norms strongly and consistently influence self‐efficacy, especially for actions observable by others, and also directly influence protective responses. Personal competencies increase self‐efficacy and support protective action, particularly with regard to preventive and structural measures. The strength and direction of the antecedents of self‐efficacy as well as of other PMT determinants vary between general and specific protective responses. This study provides important insights for risk managers, suggesting that interventions involving social norms and personal competencies can be effective in stimulating self‐efficacy and, in turn, private flood mitigation. Interventions and research should clearly differentiate between general intention and the implementation of specific measures, and should address cumulative, synergistic, or tradeoff interrelations between multiple measures.